2018
DOI: 10.1292/jvms.18-0044
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel use facilitates handling of ICR mice and decreases experimental variation

Abstract: We evaluated a handling method using tunnels to tame laboratory mice (ICR) in the context of animal welfare and ease of handling. During 1-week acclimation to handling and subsequent 1-week oral administration (once per day), voluntary interaction with the experimenter was much greater in mice handled by a tunnel compared to those picked up by the tail. According to a rating of the ease of handling laboratory mice, a tunnel facilitated mouse handling during acclimation to handling and oral gavage of saline com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 16 publications
7
51
0
Order By: Relevance
“…Considering these facts, it is highly probable that the recently recommended methods using cups and tunnels are making mice accustomed to high altitudes, and it is questionable whether they actually reduce various anxiety-like behaviours in mice. Furthermore, it has also been reported that mice undergoing tunnelling do not exhibit altered anxiety-like behaviour 32 . In this study, the mice used for comparison were held by their tails for 30 s every day by the experimenter to induce elevation-related anxiety.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering these facts, it is highly probable that the recently recommended methods using cups and tunnels are making mice accustomed to high altitudes, and it is questionable whether they actually reduce various anxiety-like behaviours in mice. Furthermore, it has also been reported that mice undergoing tunnelling do not exhibit altered anxiety-like behaviour 32 . In this study, the mice used for comparison were held by their tails for 30 s every day by the experimenter to induce elevation-related anxiety.…”
Section: Discussionmentioning
confidence: 98%
“…These studies used tools (cups and transparent tunnels) to move the mouse to a specific location, and their authors describe that these methods reduce the effect on the anxiety levels in mice. Using tunnels or cups has been recommended by additional studies as a method to reduce anxiety-like behaviour in mice if their handling is unavoidable [30][31][32] . In fact, handling tunnels and cups minimize human contact with animals, but it is impractical to perform all experimental work solely with tunnels and cups.…”
mentioning
confidence: 99%
“…Both of these methods are considered non-aversive, because they result in an increased willingness of mice to interact with their handler, and have been found to lower anxiety-like behaviour and enhance the performance of mice in standard behavioural tests [7][8][9][10][11][12]. These findings have been replicated in several laboratories with a range of mouse strains [7][8][9][10][11][12]. Where examined, the positive effects of anxiety reduction, improved exploration and interaction with a handler are similar for cup and tunnel handling methods [7,8], suggesting the benefits of using either tunnel or cup methods are similar.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that handling mice using a home-cage tunnel can also improve ease of handling during oral gavage compared to tail-handled mice [11]. Furthermore, tail-handled mice show decreased responsiveness to reward compared to tunnel handled mice, indicative of anhedonia and chronic stress [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation